¿Qué hay de acción en las clases sociales? - Mora Malo, Enrico (Nómadas. Critical Journal of Social and Juridical Science, 2008)
In this paper we put forward a whole of aspects of class analysis that it pays attention to the actions of subjects, historical actions in not chosen circumstances. The circumstances are result from past interactions that they influence the future actions. We take the concept of relation of production as a central axis of our theoretical enquiry that it starts from a heterodox Marxist framework. We consider this concept a key to develop we proposal of social class analysis that it takes the process of social interaction in social inequality conditions into account. We restrict our proposal to modern patriarchal capitalism.